2015
DOI: 10.1109/tbme.2014.2342879
|View full text |Cite
|
Sign up to set email alerts
|

A Joint QRS Detection and Data Compression Scheme for Wearable Sensors

Abstract: This paper presents a novel electrocardiogram (ECG) processing technique for joint data compression and QRS detection in a wireless wearable sensor. The proposed algorithm is aimed at lowering the average complexity per task by sharing the computational load among multiple essential signal-processing tasks needed for wearable devices. The compression algorithm, which is based on an adaptive linear data prediction scheme, achieves a lossless bit compression ratio of 2.286x. The QRS detection algorithm achieves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 30 publications
1
67
0
Order By: Relevance
“…The optimal W and q values were determined by 8 after testing various combinations of ( W , q ) with W ranging from 3 to 6 and q ranging from 9 to 17. It was found that optimal detection QRS accuracy was achieved with W  = 3 and q  = 15.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The optimal W and q values were determined by 8 after testing various combinations of ( W , q ) with W ranging from 3 to 6 and q ranging from 9 to 17. It was found that optimal detection QRS accuracy was achieved with W  = 3 and q  = 15.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Deepu et al . 8 used prediction error as a marker to locate the QRS complex in ECG signals. By contrast, Method III does not need the linear predictor step used in Method I.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations